Konstruksi Pajak Lingkungan di Indonesia - Indah Putri Rahmawati (Universitas Slamet Riyadi, 2019)
Environmental tax assessment as an environmental economic instrument is still rare. So far, environmental law studies have been limited to analyzes of administrative violations and criminal actions against the environment, which tend to be repressive. This action is also considered less effective to overcome environmental problems that increasingly apprehensive. Some research suggests, the application of environmental taxes can be used as a preventive measure against environmental damage. In 2006 Indonesia has planned the implementation of environmental taxes, but to date has not been implemented. This is due to differences of opinion due to the absence of a definite application concept. Therefore, there is a need for research on the construction of environmental taxes, based on the Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup (UUPPLH), which includes environmental economic instruments, one of them through the application of taxes. Based on this, environmental taxes should be designed as a source of fund management and addressing environmental issues for sustainable development. This is based on the important role of economic aspect in environmental management.